Marketing Strategy Analysis to Increase Competitiveness Case Study of Aisyiyah Daycare Sidoarjo: Analisis Strategi Pemasaran untuk Meningkatkan Daya Saing Studi Kasus Aisyiyah Daycare Sidoarjo - Khuzanah; Widodo, Heri (Indonesian Journal of Innovation Studies, 2026)
General Background: Daycare competition requires marketing approaches that can reach prospective parents beyond local word-of-mouth networks. Specific Background: Aisyiyah Daycare Sidoarjo relies mainly on word-of-mouth promotion and has limited digital marketing presence, while annual registrations remain below its target of 40 children. Knowledge Gap: Previous studies have examined daycare and marketing strategies, but this study specifically analyzes Aisyiyah Daycare Sidoarjo using SWOT analysis. Aims: This study analyzes marketing strategies for improving the daycare’s competitiveness. Results: Using a qualitative approach with observation, interviews, documentation, and SWOT analysis, the study identifies good reputation, experienced staff, affordable costs, and strategic location as strengths, while limited digital presence and staff technology skills are weaknesses. Novelty: The study formulates context-specific strategies combining online presence, service quality, partnerships, promotions, and parent engagement. Implications: Technology training and stronger digital marketing are recommended. Key Findings Highlights Word-of-mouth promotion limits wider audience reach. Experienced staff and local reputation are key strengths. Technology training and stronger online presence are recommended responses. Keywords: Daycare Marketing, Online Presence, SWOT Analysis, Service Quality, Parent Engagement